On two-component contact model in continuum with one independent component - Filonenko, D. O.; Finkelshtein, D. L.; Kondratiev, Yu. G. (Methods of Functional Analysis and Topology, 2008)
Properties of a contact process in continuum for a system of particles of two types, one which is independent of the other, are considered. We study dynamics of the first and the second order correlation functions, their asymptotics, and the dependence on parameters of the system.